PENERAPAN MODEL SIKLUS BELAJAR 5E UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PADA MATERI ASAM BASA - Nanda, Yufitri; Sartika, Rody Putra; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe purpose of this study was to determine difference of science process skills of SMA Muhammadiyah 1 Pontianak students before and after being taught through 5E learning cycle model on acid base material. This study was conducted in form of pre experimental design. One group pretest?posttest design was applied as research design. Independent variables were lesson before and after being taught through 5E learning cycle model. Dependent variable was science process skills. The sample in this research was class XI SMA Muhammadiyah 1 Pontianak. To collect data, assessment technique was applied and achievement test was used to get data. Data were analyzed by means of inferential and descriptive statistic. Result of statistic showed P-value = 0,000 < ? = 0.05 which means that there was a significant difference of student science process skills before and after being taught through 5E learning cycle model on acid base material. Keywords: Learning Cycle Model 5E, Science Process Skills, Acid Base Material